2020
DOI: 10.1073/pnas.1905057117
|View full text |Cite
|
Sign up to set email alerts
|

Translation of the intrinsically disordered protein α-synuclein is inhibited by a small molecule targeting its structured mRNA

Abstract: Many proteins are refractory to targeting because they lack small-molecule binding pockets. An alternative to drugging these proteins directly is to target the messenger (m)RNA that encodes them, thereby reducing protein levels. We describe such an approach for the difficult-to-target protein α-synuclein encoded by the SNCA gene. Multiplication of the SNCA gene locus causes dominantly inherited Parkinson’s disease (PD), and α-synuclein protein aggregates in Lewy bodies and Lewy neurites in sporadic PD. Thus, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
96
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 81 publications
0
96
0
Order By: Relevance
“…Particular focus is on the development of novel therapeutic agents to target and inhibit processes critical to SARS-CoV-2 infection and replication. To help address this important need, we have analyzed the SARS-CoV-2 genome using an RNA structural analysis and motif discovery pipeline, ScanFold, which has been previously applied to two other RNA viruses: Zika and HIV-1 4 ; as well as human mRNAs for MYC 5 and α-synuclein 6 . A significant innovation of ScanFold is that unique consensus secondary structural motifs are generated from bases pairs with the strongest evidence of being functional, while not necessarily focusing on evolutionary conservation (as in a recent analysis of SARS-CoV-2 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Particular focus is on the development of novel therapeutic agents to target and inhibit processes critical to SARS-CoV-2 infection and replication. To help address this important need, we have analyzed the SARS-CoV-2 genome using an RNA structural analysis and motif discovery pipeline, ScanFold, which has been previously applied to two other RNA viruses: Zika and HIV-1 4 ; as well as human mRNAs for MYC 5 and α-synuclein 6 . A significant innovation of ScanFold is that unique consensus secondary structural motifs are generated from bases pairs with the strongest evidence of being functional, while not necessarily focusing on evolutionary conservation (as in a recent analysis of SARS-CoV-2 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments that assess off-target interactions and RNA selectivity are clearly important when it comes to testing novel RNA-binders in vitro and in vivo (Naro et al 2018;Zhang et al 2020;Costales et al 2017;Abulwerdi et al 2019;Donlic et al 2018). However, our survey of the HIV-1 TAR literature ( Supplementary Table S2) revealed that these controls are not always performed (Gelus et al 1999;He et al 2005;Hwang et al 2003).…”
Section: Rnasmentioning
confidence: 99%
“…Such compounds with demonstrated cellular activity have been enumerated in the R-BIND database (Morgan et al 2019). Some of these compounds have been shown to bind specific RNAs and inhibit their cellular activities with well-validated selectivity (Costales et al 2017(Costales et al , 2019Zhang et al 2020;Shi et al 2019;Haga et al 2015;Naro et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, multiple occurrences of bulged nucleotides and internal loops within a helix can establish a structural and dynamics pattern unique to the RNA molecule containing those features. Although non-canonical elements within regular helices offer clear opportunities for targeting specific ncRNAs, progress towards the identification of small molecules that selectively bind such nonstandard features has only recently begun to gain momentum [6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%